How teachable agents influence students' responses to critical constructive feedback. Issue 1 (2nd January 2021) - Silvervarg, Annika; Wolf, Rachel; Blair, Kristen Pilner; Haake, Magnus; Gulz, Agneta
Abstract: Does a teachable agent influence the uptake or neglect of 'critical constructive feedback' and learning within a digital environment? 285 middle-school students engaged with a history learning game in a 2x2 study design. One dimension was inclusion of a teachable agent. Orthogonal was whether critical constructive feedback was presented automatically or only when students chose. Analyses showed that a teachable agent positively affected students' responses to feedback and mitigated feedback neglect; the results were especially strong for lower-achieving students. Additionally, presence of a teachable agent improved post-test performance for students overall, and this effect was mediated by lower feedback neglect.